Fearless but anxious? A systematic review on the utility of fear and anxiety levels to classify subtypes of psychopathy. (31st October 2021) - Hofmann, Miriam J.; Schneider, Sabrina; Mokros, Andreas
Abstract: Psychopathic traits have been linked to anomalies in experiencing fear and anxiety. It remains unclear, however, to what extent fear and anxiety levels are useful parameters to effectively distinguish between subtypes of psychopathy. Therefore, we aimed to elucidate whether different psychopathic phenotypes (primary and secondary psychopathy) can be delineated based on fear/anxiety levels. To investigate associations between psychopathic traits and conscious experiences of fear and/or anxiety a systematic qualitative review of studies was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Seventeen studies were included in the review. We found some evidence for attenuated fear/anxiety levels in primary psychopathy. In secondary psychopathy, the experience of fear/anxiety seemed rather intact. Moreover, primary psychopathy might be associated with a more positive appraisal of the conscious feeling of fear. We reason that consciously experienced fear and anxiety are distinctly related to primary and secondary psychopathy. Due to a lack of consistent and comprehensive operationalizations of fear and anxiety, however, conclusions about their potential to differentiate psychopathic subtypes should be drawn with caution.